Gender stereotyping in portuguese children living in Portugal and abroad: effects of migration, age, and gender - Félix Neto (1997)
Williams and Best's (1990) study of the development of sex stereotype knowledge among young children in 24 countries was extended to Portuguese subjects living in Portugal and abroad. Subjects were 720 children (aged 8-11 years), with each age group evenly divided by gender, and each age/gender group evenly divided into three places of residence: urban and rural areas in Portugal and in France. Subjects were administered the Sex Stereotype Measure II (SSM II) in which children select between male and female silhouettes as the person described in brief stories containing highly sex-typed psychological characteristics (aggressive, emotional, etc.). The results of the study indicated an increase in sex stereotype knowledge from 8 to 11 years, a greater knowledge of the migrants' children in France than of the children living in urban and rural areas in Portugal, and a greater knowledge of female stereotype traits than male stereotype traits.